Comprehensive health evaluation of workers in the ceramics industry. Issue 2 (February 1993) - Huang, J; Shibata, E; Takeuchi, Y; Okutani, H
Abstract : A cross sectional study on ceramics workers in the Seto area of Japan was conducted to determine whether there are differences in the morbidity pattern and overall health among the working populations employed by different sized companies engaged in the ceramics industry. The study population consisted of 3324 male ceramics workers (age range 40-69) who participated in the Seto occupational health screening programme in 1990. The prevalences of pulmonary diseases (silicosis and tuberculosis) and findings of some nonpulmonary diseases were compared in terms of company size by categories of 1-19, 20-49, 50-99, and 100 or more employees. The values of various screening tests were subjected to principle component analysis to extract factors representing key indices of health state. The average factor scores stratified by company size were used to quantitatively evaluate the comprehensive health level. Both prevalence and multivariate analysis showed that the employees working for smaller companies had overall worse health. The smaller the company, the higher the prevalence and the lower the health scores for silicosis and pulmonary tuberculosis tended to be; significantly increased rates and lower health scores for hypertension, anaemia, and glucosuria among small companies were also found when compared with larger companies. The high morbidity of silicosis and pulmonary tuberculosis in smaller companies contributed most to the decline in the overall health level.